Reformation of Law Administration in Jean Domat‘s Masterworks - Alberto Iglesias Garzón (Journal on European History of Law, 2011)
The quest for clarity and legal security in Jean Domat´s legal thought binds his masterwork Les Loix Civiles dans leur Ordre Naturel (1689-1694) to the process of reformation of the judiciary administration in Louis XIV´s France. It is also through this perspective that his legal and philosophical thought reaches the 1804 French civil code. Overcoming medieval jurisprudence and its substitution by sovereign´s law as the main source of legal creation will influence Jean Domat. His great concern about what he thought to be the “false groundings of jurisprudence” came along with his concern about judges not respecting the sovereign´s law. The whole of his legal view is about the increasing absolute power of the king and his means to the unification of law. Aiming to the suppression of the judge´s discretionary legal practice and making him bounded to the sovereign´s law was a certain way to controlling the non-conformist members of the judiciary administration. The main argument for implementing Domat´s view was the (divine) perfection of roman law.